Changes in patterns of biodiversity of marine mollusks along the Brazilian coast during the late Holocene inferred from shell-mound (sambaquis) data. (November 2016) - Souza, Rosa CCL; Lima, Tania A; Duarte, Michelle Rezende; Silva, Edson P
An archaeological dimension expands the concept of biodiversity by generating long-term perspectives, combining multiple approaches and methodologies to enhance understanding of environmental changes. Aiming to investigate the patterns of biodiversity of marine mollusks over time, a comparison was made between three sets of archaeological sites (shellmounds) located in three geographic areas of the south-southeastern Brazilian coast. Sites dated between 1000–2000 and 4000–5000 yr BP were analyzed. A total of 37 bivalves and 26 gastropods were recorded. To describe the malacological community two indices of taxonomic diversity were used: average taxonomic distinctness and variation in taxonomic distinctness. The results showed a tendency of reduction in biodiversity patterns in the last 5000 years measured as average taxonomic distinctness. The observed reduction in biodiversity does not seem to be directly related to climate change over the period and there is a lack of data which could demonstrate any association between reduction in biodiversity and cultural causes such as preferences, technical level or food taboos of the prehistoric human populations. On the other hand, changes in sea level during this period are well documented and have been responsible for dramatic changes along the coast of this region. Therefore, it is likely that it could have affected local biodiversity and caused the observed pattern.